SPE Asia Pacific Oil and Gas Conference and Exhibition 2018
DOI: 10.2118/192015-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Alkalinity for EOR Purposes in Sandstone Reservoirs

Abstract: With increased environmental focus and sustainability, classical water-based EOR with surfactants or polymers meet larger implementation scepticism. This has increased the attention toward water-based EOR methods with low environmental impact and lower costs, such as Smart Water and alkaline flooding. Both methods are based on the establishment of alkaline conditions in the formation. Chemical interactions among the rock minerals, reservoir fluids, and injection brine can be reflected in the pH of the produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Smart water EOR effects are associated with chemical imbalance, when FW is replaced by smart water brine. This may result in a series of ion exchange reactions and, ultimately, a change in pH of the water phase toward more alkaline . Alkaline environment can promote the formation of nonprotonated crude oil components, eqs and , which have lower affinity toward negatively charged sandstone minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Smart water EOR effects are associated with chemical imbalance, when FW is replaced by smart water brine. This may result in a series of ion exchange reactions and, ultimately, a change in pH of the water phase toward more alkaline . Alkaline environment can promote the formation of nonprotonated crude oil components, eqs and , which have lower affinity toward negatively charged sandstone minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have previously shown that the potential for successful smart water EOR implementation in sandstones is associated with a pH development during LS smart water injection. ,, The pH development rate, in turn, is dependent on rock mineralogy, that is, cation-exchange reactions at the mineral–brine interface, and on FW composition . The presence of acidic gases in the reservoir, such as H 2 S and CO 2 , may also influence both initial reservoir pH and the magnitude of pH increase during smart water injection.…”
Section: Resultsmentioning
confidence: 99%